PjBL Etno-STEM: Implikasi terhadap Kreativitas Produk dan Kesadaran Lingkungan Peserta Didik - Yolanda, Helen; Amelia, Rizki Nor (Mahesa Research Center, 2026)
Context-based learning is essential to enhance students’ creativity and environmental awareness. Project-Based Learning (PjBL) based on Ethno-STEM is an approach that integrates local wisdom with science and technology. This study aimed to analyze differences in product creativity and environmental awareness between Ethno-STEM-based PjBL and Discovery Learning. A quasi-experimental design was employed with experimental and control groups in science learning. Data were analyzed using descriptive and inferential statistics through an Independent Samples t-test. Product creativity was measured based on product assessment scores, while environmental awareness was assessed using gain scores (post-test minus pre-test). The results showed that the experimental group’s product creativity (M = 51.80; SD = 3.71) was higher than that of the control group (M = 41.57; SD = 2.20), with a significant difference (t = 7.49; p 0.05). Environmental awareness increased in both groups; however, no significant difference was found (t = –0.588; p 0.05). Therefore, Ethno-STEM-based PjBL is effective in improving students’ product creativity, but enhancing environmental awareness requires more sustained and continuous interventions.